In vitro and in vivo trypanocidal activity of H2bdtc-loaded solid lipid nanoparticles. - Zumira A Carneiro; Pedro I da S Maia; Renata Sesti-Costa; Carla D Lopes; Tatiana A Pereira; Cristiane M Milanezi; Marcelo A Pereira da Silva; Renata F V Lopez; João S Silva; Victor M Deflon (PLoS Neglected Tropical Diseases)
The parasite Trypanosoma cruzi causes Chagas disease, which remains a serious public health concern and continues to victimize thousands of people, primarily in the poorest regions of Latin America. In the search for new therapeutic drugs against T. cruzi, here we have evaluated both the in vitro and the in vivo activity of 5-hydroxy-3-methyl-5-phenyl-pyrazoline-1-(S-benzyl dithiocarbazate) (H2bdtc) as a free compound or encapsulated into solid lipid nanoparticles (SLN); we compared the results with those achieved by using the currently employed drug, benznidazole. H2bdtc encapsulated into solid lipid nanoparticles (a) effectively reduced parasitemia in mice at concentrations 100 times lower than that normally employed for benznidazole (clinically applied at a concentration of 400 µmol kg(-1) day(-1)); (b) diminished inflammation and lesions of the liver and heart; and (c) resulted in 100% survival of mice infected with T. cruzi. Therefore, H2bdtc is a potent trypanocidal agent.